Analysis of Geomorphometric Features in the Baba Omar Valley Basin (A Study in Applied Geomorphology) - طالب, جزا توفيق; امين, هيرو نصرالدين محمد; امين, هێمن نصرالدين محمد (Sulaimani Journal for Humanities, 2019)
The present study is investigated of analyzing geomorphometric properties of Baba Omar watershed, it is regarded as a seasonal valley system in south eastern of Iraqi Kurdistan region at the beginning of the Sub-mountain area which known as foothill zone. It is lies between two contour lines (350-1100m) a.s.l, astronomically the watershed is located between two latitudes (35° 01 32 - 35° 04 20 ) north, and two longitudes (45° 32 10 - 45° 37 30 ) east, the area of the watershed is (14.06 km2 ) and pours to the Sirwan river in fifth order. The objective of the study is to identify form factor and development of Baba Omar watershed and analyze of the morphometric properties, also this study helps in the achievement of other academic researches. In order to achieve the objectives of the study, it is divided in to two sections (factor affected the formation of the watershed and geomorphological development, morphometric properties of the watershed). The study is found out that the rock composition, topographic characteristics and climate condition of the watershed contributed to activation geomorphic processes, especially vertical erosion which led to a higher drainage density of the basin, also Baba Omar valley regarded as a complex geomorphic phenomenon in the area, that considered as an interesting tourist area for climbers and adventurers, also mass wasting is predicted, rather than believing in the existence of myths and superstitious beings.